Pola Alih Tutur Percakapan dalam Film Warkop DKI Reborn: Jangkrik Boss! Part 1 - Fandi Zuliyanto; Ary Setyadi; Sri Puji Astuti (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
This research is to describe the closest speech and how to get the turn-taking of film Warkop Dki Reborn: Jangkrik Boss! Part 1. The data collection method used observation and note techniques. The theory applied is study of oral discourse: Turn-taking. Based on research, the film has the closest speech consisting of, (1) greetings followed by greeting , (2) calls followed by answer, (3) questions followed by answer. (4) offered followed by receiving, (5) offered followed by rejecting, (6) accused followed by rejecting, (7) request followed by granting, (8) requesting followed by rejecting, (9) praise followed by receiving, (10) complaints followed by reasons, (11) ) requests followed by approval, (12) command followed by acceptance, (13) command followed by rejection. In addition, the film has speech shift consisting of, (1) getting category, (2) creating, (3) stealing, (4) continuing, and (5) grab category.